Learning Obstacles of Islamic Junior High School Students on Angle Concepts - Hajar, Yuni; Suryadi, Didi; Usdiyana, Dian (International Journal of STEM Education for Sustainability, 2023)
Angle is one of the concepts from the field of geometry that is important for students to learn because there are basic concepts of geometry that can be used in other fields of mathematics and everyday life. Students still experience learning obstacles in angle concepts. This study aimed to identify learning obstacles experienced by Islamic junior high school students in angle concepts. The research method used is a qualitative method with a phenomenological approach. The samples in this study were 8-grade students and mathematics teachers from one of the Islamic junior high schools in Bandung district, Indonesia. The results show that students experience learning obstacles, and can be concluded as follows, (1) instrumental ontogenic obstacles, caused by students not being used to facing difficult problems; (2) conceptsual ontogenic obstacles, caused by low mastery of prerequisite concepts; (3) psychological ontogenic obstacles, caused by low student interest in learning; (4) epistemological obstacles, caused by low mastery of angle concepts.